2020
DOI: 10.1111/bjh.16671
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Band 3 tyrosine phosphorylation: a new mechanism for treatment of sickle cell disease

Abstract: Summary Many hypotheses have been proposed to explain how a glutamate to valine substitution in sickle haemoglobin (HbS) can cause sickle cell disease (SCD). We propose and document a new mechanism in which elevated tyrosine phosphorylation of Band 3 initiates sequelae that cause vaso‐occlusion and the symptoms of SCD. In this mechanism, denaturation of HbS and release of heme generate intracellular oxidants which cause inhibition of erythrocyte tyrosine phosphatases, thus permitting constitutive tyrosine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 63 publications
0
75
0
Order By: Relevance
“…SCD is due to the modification of a single gene on chromosome 11, which will lead to a loss of membrane deformability of the red blood cell, increased RBC‐endothelial cell adhesion, and development of severe systemic vasculopathy. Endothelial activation plays a central role in the pathophysiology of vaso‐occlusion in SCD along with a now well acknowledged discharge of microparticles and release of free hemoglobin [9]. Resistance to malaria of patients carriers of hemoglobinopathies is a complex phenomenon that has been linked to adaptation of the host response with parasite sequestration and cytoadherence to endothelium [10].…”
Section: Patient 1 2mentioning
confidence: 99%
“…SCD is due to the modification of a single gene on chromosome 11, which will lead to a loss of membrane deformability of the red blood cell, increased RBC‐endothelial cell adhesion, and development of severe systemic vasculopathy. Endothelial activation plays a central role in the pathophysiology of vaso‐occlusion in SCD along with a now well acknowledged discharge of microparticles and release of free hemoglobin [9]. Resistance to malaria of patients carriers of hemoglobinopathies is a complex phenomenon that has been linked to adaptation of the host response with parasite sequestration and cytoadherence to endothelium [10].…”
Section: Patient 1 2mentioning
confidence: 99%
“…During previous studies of human erythrocyte membranes, we observed that tyrosine phosphorylation of the erythrocyte transmembrane protein, band 3, promotes dissociation of the spectrin-based membrane cytoskeleton from the lipid bilayer via a mechanism that involves an intramolecular association of the phosphorylated cytoplasmic domain of band 3 (cdb3) with an SH2-like (MESH) sequence within the membrane-spanning domain of band 3 [ 20 , 21 ]. Because this phosphorylation-induced cytoskeleton dissociation was found to cause membrane vesiculation and fragmentation [ 20 22 ], and since band 3 was observed to become increasingly tyrosine phosphorylated during maturation of Plasmodium falciparum within infected erythrocytes [ 23 , 24 ], we hypothesized that egress of the parasite from its red blood cell (RBC) host might require the parasite-stimulated tyrosine phosphorylation of band 3 in order to weaken the RBC membrane in preparation for parasite escape. A subsequent search for possible P .…”
Section: Introductionmentioning
confidence: 99%
“…SLCs are relevant to therapeutics of several human diseases and to drug discovery, either as drug targets themselves or as mediators of drug uptake (Cesar-Razquin et al, 2015). It now seems likely that the varying expression of SLCs with overlapping selectivities, as well as their regulation by post-translational modification, will also contribute to pathology and provide opportunities for therapeutic development (Noomuna et al, 2020). Importantly, our data provide a framework for systemwide studies of SLC small molecule flux and signaling throughout the differentiation process.…”
Section: Discussionmentioning
confidence: 85%